STUDENTS’ SPEAKING SKILLS THROUGH PROJECT BASED LEARNING AT ELEMENTARY SCHOOLS - Fajjar Ajrin Astiar; Rarasaning Satiangingsih; Via Yustitia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Students need speaking skills to express their opinions in front of the class; however, many students still lack confidence in speaking. This study aimed to investigate whether students taught using the Project-Based Learning (PjBL) model had better speaking skills than those taught using the cooperative learning model. This research employed a quasi-experimental design with a Posttest-Only Control Group design. The population consisted of fifth-grade students at SDN Gayungan II Surabaya, and samples were selected using cluster random sampling, with class V-A as the experimental class and class V-B as the control class. Data were collected through tests, observations, and documentation. Test data were analyzed using inferential statistics with SPSS, while data from student activities and learning implementation were analyzed descriptively. The results showed that students taught using the PjBL model had significantly better speaking skills than those taught using the cooperative learning model.